SCIB1, a huIgG1 antibody DNA vaccination, combined with PD-1 blockade induced efficient therapy of poorly immunogenic tumors - Xue, Wei; Brentville, Victoria A.; Symonds, Peter; Cook, Katherine; Yagita, Hideo; Metheringham, Rachael L.; Durrant, Lindy (Impact Journals, 2016)
Purpose: We have previously shown that supraoptimal signaling of high avidity T cells leads to high expression of PD-1 and inhibition of proliferation. This study was designed to see if this effect could be mitigated by combining a vaccine that stimulates high avidity T cells with PD-1 blockade.